2009
DOI: 10.1164/rccm.200812-1949oc
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells in Preterm Infants with Bronchopulmonary Dysplasia

Abstract: ECFCs are low at extremely low gestational ages and increase during gestation; extremely preterm infants who display lower numbers at birth have an increased risk of developing BPD. Our findings suggest that decreased ECFCs following extremely preterm birth may be associated with the risk for developing lung vascular immaturity characteristic of new BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
6
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 21 publications
7
104
6
19
Order By: Relevance
“…In addition, human fetal lung ECFC and newborn rat ECFC function are also impaired after high oxygen exposure (mimicking preterm birth conditions) 36. EPC dysfunction in preterm cord blood, particularly the ECFC, has been associated with the development of BPD 56, 57. BPD is characterized by disrupted alveolar and lung vasculogenesis, and is considered an early manifestation of an impaired angiogenic capacity in preterm newborns 26.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, human fetal lung ECFC and newborn rat ECFC function are also impaired after high oxygen exposure (mimicking preterm birth conditions) 36. EPC dysfunction in preterm cord blood, particularly the ECFC, has been associated with the development of BPD 56, 57. BPD is characterized by disrupted alveolar and lung vasculogenesis, and is considered an early manifestation of an impaired angiogenic capacity in preterm newborns 26.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, ECFC colony count was decreased in infants with decreasing gestational age [5]. In another study, Baker et al found the opposite -preterm cord blood had a higher ECFC colony count and growth rate compared to term cord blood [23].…”
Section: Endothelial Colony Forming Cells (Ecfcs) and Bpdmentioning
confidence: 96%
“…Two studies have shown that ECFCs are decreased in cord blood samples of preterm infants who subsequently develop BPD as compared to preterm infants with mild or no BPD [5,23]. These assays were done using cord blood taken at birth before exposure of the infants to postnatal stress and before they developed BPD and so represent a predisposition to illness as opposed to a reaction to a biological challenge.…”
Section: Endothelial Colony Forming Cells (Ecfcs) and Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…EPCs is one of the key cells mediating vascular growth, which can mobilize from bone marrow and home to the site of vascular injuries, promoting neovascularization (5). There is data showing that reduced numbers or dysfunction of EPCs at birth is associated with the development of BPD (6,7). In addition, a reduction in the number of EPCs in the bone marrow, circulation and lungs has also emerged in animal models of BPD (8).…”
mentioning
confidence: 99%